Quantum chemistry beyond Born–Oppenheimer approximation on a quantum computer: A simulated phase estimation study. Issue 18 (22nd June 2016) - Veis, Libor; Višňák, Jakub; Nishizawa, Hiroaki; Nakai, Hiromi; Pittner, Jiří
Abstract : We present an efficient quantum algorithm for beyond‐Born–Oppenheimer molecular energy computations. Our approach combines the quantum full configuration interaction method with the nuclear orbital plus molecular orbital method. We give the details of the algorithm and demonstrate its performance by classical simulations. Two isotopomers of the hydrogen molecule (H2, HT) were chosen as representative examples and calculations of the lowest rotationless vibrational transition energies were simulated. © 2016 Wiley Periodicals, Inc. Abstract : While the best known classical algorithm for full configuration interaction scales exponentially, algorithms for a quantum computer provide polynomial scaling (i.e. are efficient). This also allows for efficient beyond‐Born‐Oppenheimer full configuration interaction calculations. Two isotopomers of the hydrogen molecule (H2, HT) were chosen as representative examples and calculations of the lowest rotationless vibrational transition energies were simulated.